2014
DOI: 10.1080/01634372.2014.895472
|View full text |Cite
|
Sign up to set email alerts
|

“They Just Don’t Have a Clue”: Transgender Aging and Implications for Social Work

Abstract: This article explores transgender aging, drawing from life story interviews with transgender adults aged 62-78. The analysis focuses on 3 themes: intersections of age and gender during the life course, lack of knowledge of transgender issues, and how previous experiences of accessing care and social services matter in later life. It illustrates how older transgendered adults carry physical and mental scars from previously encountered transphobia, which affect various aspects of later life. Implications for soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
128
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(132 citation statements)
references
References 20 publications
2
128
0
2
Order By: Relevance
“…Participants younger than 50 years were included in 21.1% of the studies, which incorporated age-based comparisons. While the majority of the studies reported on a USA sample (73.2%), 4 studies reported on international samples [22-25]; 21.1% had samples exclusively from outside the USA, including Australia [26, 27], Canada [28, 29], Hong Kong [30], Israel [31], the Netherlands [32, 33], New Zealand [34, 35], Sweden [36], and the UK [18, 37-39]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants younger than 50 years were included in 21.1% of the studies, which incorporated age-based comparisons. While the majority of the studies reported on a USA sample (73.2%), 4 studies reported on international samples [22-25]; 21.1% had samples exclusively from outside the USA, including Australia [26, 27], Canada [28, 29], Hong Kong [30], Israel [31], the Netherlands [32, 33], New Zealand [34, 35], Sweden [36], and the UK [18, 37-39]. …”
Section: Resultsmentioning
confidence: 99%
“…In a population-based study, sexual-minority older women were more likely than heterosexual women to experience financial barriers to health care [20]. Additional barriers included difficulty locating needed services [78], past negative experiences in care settings [57, 78], and fears of discrimination [24, 36, 63, 79]. Despite barriers to care, compared to heterosexuals, sexual minorities reported higher service use in some areas.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However both bodies of literature are predominantly based on the experiences of older gay men and, to a lesser extent, older lesbians, meaning that little can be deduced about the distinctive experiences of transgender and bisexual people (Barker et al, 2012). Transgender people's later life experiences are beginning to be addressed empirically (Fredriksen-Goldsen, Cook-Daniels, et al, 2014;Siverskog, 2014;Witten, 2016) but much is still not known.…”
Section: Introductionmentioning
confidence: 99%